The Increase Of Podcast Interest Among Gen Z: The Development Of Social Reality Through Podcasts - Azhari Putri Aulia; Aji Satya Pujastra; Tadeu Amaral Sarmento; Alan Verdiyan Tandjung; Ruslan Ramli (Riviera Publishing, 2025)
This research examines the increasing interest of Generation Z in Indonesia in podcasts, and how audiovisual elements - especially on the YouTube platform - shape social reality. The problem raised stems from the increasing consumption of digital media by Gen Z and the shifting function of podcasts which are now not only as entertainment, but also as a means of identity formation and social awareness. The main objective of this research is to analyze the influence of visual elements in podcast content on audience engagement and social perception. The research uses a qualitative approach with a desk study method, with secondary data collected from academic journals, digital reports, and media publications in the last five years. The data was analyzed thematically to identify Gen Z's podcast consumption behavior patterns. The results show that Generation Z prefers podcast content that integrates audio and visual elements, such as those presented on YouTube. Visualizations such as facial expressions, animations, and real-time reactions enhance comprehension while creating deeper emotional engagement. Unlike audio-only platforms, YouTube allows for participatory interaction and community building around podcast content. These features contribute to shaping social narratives and strengthening digital literacy among young audiences. The implications of this research point to the need for content creators and the media industry to prioritize interactive and visually rich podcast formats. In addition, educational institutions and policy makers can utilize podcasts as a medium for digital education, identity formation, and strengthening citizen participation in the digital era.